AN ASSESSMENT OF CUBAN FOOD SECURITY BASED ON THE AGRICULTURAL AREA UNDER CULTIVATION AND AGRICULTURAL YIELDS - Cosío, E.C.; Suárez del Villar, Alexis; Álvarez Sánchez, Ana; Cruz, I.A. (My University, 2022)
The research was carried out with official data published in the country, collected from official information sources from 2007 to 2019. In the variables analyzed, the following were considered as having high explanatory power: land distribution, total area, agricultural area, cultivated area, yields of selected crops. For the calculation of the nutritional needs of the population, the nutritional recommendations for the Cuban population were taken into account and the productions were grouped ac-cording to the classification established for the food groups in Cuba. The country’s agricultural area is 6400.18 Mha in 2019, which its use decreases for all the items studied, except for banana, bell pepper, bean, lemon, guava and pump fruit. In addition, yields of the main crops are low, as is the productivity of the livestock sector analyzed. To contribute to the achieve-ment of food security for the Cuban population in correspondence with the standards of the National Institute of Nutrition, an area with technological package (irrigation and optimal yields) of 3942577.82 ha is needed, existing agricultural area in the country; and without technological package (without irrigation), an area of 6424285.82 ha, which are insufficient in 23485 ha. © 2022, University of Cienfuegos, Carlos Rafael Rodriguez. All rights reserved.
DE LA SEGURIDAD ALIMENTARIA CUBANA A PARTIR DE LA SUPER-FICIE AGRÍCOLA EXPLOTADA Y LOS RENDIMIENTOS AGRÍCOLAS